Applied Study on Analysis of Fixed, Random and Mixed Panel Data Models Measured at specific time intervals - مجيد رجاء كامل (Journal of Economics and Administrative Sciences, 2017)
This research sought to present a concept of cross-sectional data models, A crucial double data to take the impact of the change in time and obtained from the measured phenomenon of repeated observations in different time periods, Where the models of the panel data were defined by different types of fixed , random and mixed, and Comparing them by studying and analyzing the mathematical relationship between the influence of time with a set of basic variables Which are the main axes on which the research is based and is represented by the monthly revenue of the working individual and the profits it generates, which represents the variable response And its relationship to a set of explanatory variables represented by the years of service of the working individual and the academic achievement of him and the classifier starting with (graduates of the intermediate school or below, graduates of the preparatory school, graduates of institutes, graduates of colleges and universities) Finally sex was divided into two categories: male and female The sample of the research is a group of individuals (100) individuals working in private sector companies with different commercial agencies in Baghdad with financial, administrative, technical, sales and services sectors, namely, the research community And then to extract the estimates of the parameters of the models and the Variations of errors as well as their testing and analysis where it was observed how to control the heterogeneity of variance and increase in degrees of freedom and less multicollinearity among the variables, which illustrates the efficiency and importance and accuracy of this type of models and their importance in making sound decisions and reliable results The results also showed the importance of the years of service on the performance of the working individual and the increase in productivity and efficiency, adding to the practical experience of utmost importance, as well as distinguished individuals working in the achievement of university degree on the rest of the other educational collections.